Evidence for increase in finger blood flow, evaluated by laser Doppler flowmetry, following iloprost infusion in patients with systemic sclerosis: a week-long observational longitudinal study. (4th July 2018) - Rotondo, C; Nivuori, M; Chialà, A; Praino, E; Matucci Cerinic, M; Cutolo, M; Lapadula, G; Iannone, F
Abstract : Objectives : Iloprost plays an important role in the treatment of Raynaud's phenomenon (RP), but has transient vasodilatory effects owing to its very short half-time. We aimed to evaluate short- and medium-term haemodynamic effects of iloprost by measuring dorsal finger microvessel blood flow using laser Doppler flowmetry (LDF), in patients with RP associated with systemic sclerosis (SSc). Method : In 24 consecutive SSc patients with RP (disease duration 10.5 ± 1.3 years), LDF with heating probes was used to measure blood flow in four fingers by occlusive and heating tests, at baseline, after 3 consecutive days of iloprost infusion, and at 24 h and 7 days after last iloprost infusion. Nailfold videocapillaroscopy (NVC) patterns of microvascular damage were investigated. Sixteen healthy controls were studied to compare baseline flows. Results : Compared to controls, SSc patients showed significantly impaired axon reflex vasoregulation and nitric oxide responses at baseline (p = 0.001 and p = 0.03, respectively). After iloprost, a prompt but transient significant improvement in endothelial-dependent vasodilation (occlusive test) was seen only in SSc patients with an 'active' NVC pattern (p ≤ 0.05). The iloprost effects vanished within 7 days after the last infusion. No significant differences were found, in the whole study, between patients with and without digital ulcers. Conclusions : Microcirculatory blood flow increases following 3 days of iloprost infusion but fades shortly after treatment. Although iloprost is effective in reducing the severity of RP in SSc, the most suitable regimen and timing to obtain longer lasting vasodilatory benefits remain to be established.